Pioneers of African Studies in Kraków: In memory of Professor Roman Stopa (1895-1995) - Kłosowicz, Robert; Stępień, Miłosława (2020)
This publication, entitled Pioneers of African Studies in Kraków, aims to present the beginnings of African Studies in Kraków, which has currently been largely forgotten, while in fact it was in Kraków in the first decades of the 20th century that Bronisław Malinowski (1884-1942) launched his career at the Jagiellonian University, his first Alma Mater, at which he defended his PhD thesis in philosophy in 1908.For Kraków-based African studies, the 1930s were a turning point, during which the developing interest in Africa would bear fruit in the form of the first independent research projects conducted in the field – on the African continent. The best example would be the studies conducted by Roman Stopa (1895-1995), considered to be the father of Polish research into African linguistics, a professor of the Jagiellonian University, a world-renowned expert on click languages. The first part of this book is dedicated to Professor Roman Stopa, and the second part is dedicated to the African studies in Kraków after World War II.